A meta-analysis of hairy vetch as a previous cover crop for maize - Rodriguez, Maria Pia; Vargas, Joaquín; Correndo, Adrián; Carcedo, Ana Julia Paula; Carciochi, Walter Daniel; Sainz Rozas, Hernan Rene; Barbieri, Pablo; Ciampitti, Ignacio Antonio (Elsevier, 2024)
Background The use of hairy vetch (Vicia villosa Roth.) as cover crop is increasing worldwide. Hairy vetch can contribute as a nitrogen (N) source with potential to impact subsequent high N demanding cereals such as maize (Zea mays L.). Contrasting literature results emphasize the need for a global synthesis analysis to quantify changes in maize yield after hairy vetch. Objectives A meta-analysis was conducted to i) quantify maize yield response to hairy vetch as previous crop, ii) explore hairy vetch influence on fertilized and non-N fertilized maize yields, and iii) assess the tillage and environment factors on maize yield response to hairy vetch. Methods The global systematic search yielded 23 publications selected by the following criteria, i) hairy vetch dry matter at the end of the season, ii) maize grain yield, and iii) experimental design with (Mzhv) and without (Mzcontrol) hairy vetch treatments. Information such as N fertilization for maize, N accumulation in hairy vetch, organic matter, and tillage before maize sowing were recorded. Hairy vetch effects (effect size) were expressed as a ratio (percentage of grain yield variation in Mzhv/Mzcontrol). Results Under non-N fertilization (n = 9), results revealed hairy vetch had mostly a positive effect, ranging from 13 to 45% (n = 6). In contrast, N-fertilized maize (n = 20) showed a high chance of neutral effects (n = 12), moderate probability of positive yield impact (7 to 38%, n = 6), and a low likelihood of negative effects (−32 and −17%, n = 2). Notably, maize yields improved by 21–25% when the N accumulation in hairy vetch ranged from 95 to 150 kg ha−1 and N rate from 0 to 120 kg ha−1. Non-N-fertilized maize exhibited a 14% increase in response in no-till systems and a 31% increase with conventional tillage. Conclusion This study summarizes potential benefits of hairy vetch preceding maize. Yet, the heterogeneous outcomes deserve further exploration in terms of environment and management factors